Constituting De-Colonializing Horizons: Indigenous Theology, Indigenous Spirituality, and Christianity - Opas, Minna (Religious studies and theology, 2017)
Indigenous Theology was born in Central and South America in the 1950s and 1960s in response to a demand for contextual theology, which takes into account local socio-cultural realities and, in particular, the specific needs of the poor and the marginalized indigenous peoples in these contexts. The fact that for many indigenous peoples in Central and South America Christianity stood and stands for conquest, colonialism, discrimination, and the repression of indigenous lifeways has not inhibited the development of indigenous Christian theologies. Rather, within indigenous theologies, Christianity, with its controversial history, is seen to stand in a productive tension with Indigenous Spirituality. This paper examines this productive tension between Indigenous Christianity, Indigenous Spirituality and Western Christianity. It asks how both Christianity and indigenous spiritualities become (re)presented, (re)positioned and made meaningful—co-constituted—in relation to one another in a variety of ways in the public discourses of the World Council of Churches and Central and South American Indigenous Theologians. The paper shows how, from the point of view of indigenous theologies, to be simultaneously indigenous and Christian is to be engaged in an ongoing problematizing of questions of authenticity.